2017
DOI: 10.1037/met0000100
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of Bayesian articles in psychology: The last 25 years.

Abstract: Although the statistical tools most often used by researchers in the field of psychology over the last 25 years are based on frequentist statistics, it is often claimed that the alternative Bayesian approach to statistics is gaining in popularity. In the current article, we investigated this claim by performing the very first systematic review of Bayesian psychological articles published between 1990 and 2015 (n = 1,579). We aim to provide a thorough presentation of the role Bayesian statistics plays in psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
222
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(227 citation statements)
references
References 162 publications
(206 reference statements)
2
222
0
3
Order By: Relevance
“…They also produce Bayes factors (BF)ratios of probabilities of data given null and alternative hypothesiswhich helps quantify evidence that the data provide for the null or alternative hypothesis on a continuous scale (Jeffreys, 1961;Kass & Raftery, 1995). In this study, we reported BF expressing the probability of the data given 11 JASP is a promising new programme that is gaining in popularity for Bayesian analyses (van de Schoot, Winter, Ryan, Zondervan-Zwijnenburg, & Depaoli, 2017). It features both classical and Bayesian implementations of popular statistical tests in psychological research, including correlations, t-tests, ANOVAs, regression analyses, and others.…”
Section: Covert and Overt Strategiesmentioning
confidence: 98%
See 1 more Smart Citation
“…They also produce Bayes factors (BF)ratios of probabilities of data given null and alternative hypothesiswhich helps quantify evidence that the data provide for the null or alternative hypothesis on a continuous scale (Jeffreys, 1961;Kass & Raftery, 1995). In this study, we reported BF expressing the probability of the data given 11 JASP is a promising new programme that is gaining in popularity for Bayesian analyses (van de Schoot, Winter, Ryan, Zondervan-Zwijnenburg, & Depaoli, 2017). It features both classical and Bayesian implementations of popular statistical tests in psychological research, including correlations, t-tests, ANOVAs, regression analyses, and others.…”
Section: Covert and Overt Strategiesmentioning
confidence: 98%
“… JASP is a promising new programme that is gaining in popularity for Bayesian analyses (van de Schoot, Winter, Ryan, Zondervan‐Zwijnenburg, & Depaoli, ). It features both classical and Bayesian implementations of popular statistical tests in psychological research, including correlations, t ‐tests, ANOVAs, regression analyses, and others.…”
mentioning
confidence: 99%
“…However, the biggest advantage is that the resulting score in the form of an estimate of the true score in the form of the highest quality score, which is plausible values, so that when used in a further analysis like regression analysis, it would produce a very good estimate. Other advantages of using the Bayesian approach can be seen in various literature (see, van de Schoot et al, 2014;van de Schoot, Winter, Ryan, Zondervan-Zwijnenburg, & Depaoli, 2017). Speaking of which, in this research, the Bayesian CFA used to test construct validity is the Indonesian version of GSES-12.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been increased interest in Bayesian analysis in many disciplines; for example, see the systematic reviews in the fields of educational science (König & van de Schoot, 2017), organizational science (Kruschke, 2010), psychometrics (Rupp, Dey, & Zumbo, 2004), health technology (Spiegelhalter, Myles, Jones, & Abrams, 2000), epidemiology (Rietbergen, 2017), medicine (Ashby, 2006), and psychology (Van de Schoot, Winter, Ryan, Zondervan-Zwijnenburg, & Depaoli, 2017). Also, the use of Bayesian analyses in the field of psychotraumatology was advocated during a meeting of the International Society for Traumatic Stress Studies (ISTSS) global meetings program 1 .…”
Section: Introductionmentioning
confidence: 99%